2019
DOI: 10.1111/bjet.12871
|View full text |Cite
|
Sign up to set email alerts
|

Motivational profiles and their correlates among students in virtual school foreign language courses

Abstract: Motivation is a key factor in predicting K‐12 students' online learning success. Drawing on self‐determination theory, this study used a person‐centered approach to identify the motivational profiles of students taking online high school language courses, and to examine such profiles' relationships to their learning outcomes, genders and reasons for enrollment. Cluster analysis of 466 students revealed the existence of four profiles: high and low quantity, and good and poor quality. Students in the high‐quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…Specifically related to children and adolescents, the CDC ( 2020b ) underscored that pandemic-induced trauma may have long-term consequences. As a result, a toolkit for parents with suggestions to support the social, emotional, cognitive, and physical health of children was developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically related to children and adolescents, the CDC ( 2020b ) underscored that pandemic-induced trauma may have long-term consequences. As a result, a toolkit for parents with suggestions to support the social, emotional, cognitive, and physical health of children was developed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because younger learners need much more support for interacting with content via technology, online experiences for K-5 learners are typically facilitated in the physical classroom with the teacher present ( Digital Learning Collaborative, 2019 ). Regarding existing studies of high school WL learners, scholars have explored learners’ perceptions of online learning ( Oliver, Kellogg, & Patel, 2012 ; Zhang & Lin, 2020a ) and motivational factors ( Zhang & Lin, 2020b ) and their relationships to course outcomes. Oliver et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a constructivist learning environment is established and reinforced when educators and learners interact in a manner that demonstrates genuine caring for each other, which in turn translates into increased learning and teaching efficacy [25]. Furthermore, the research found convincing evidence for the correlation between constructivist teaching approaches and a positive learning environment [26], further research should be conducted to identify individual variables of student demographics to determine the effective online teaching strategies.…”
Section: Outcome and Analysismentioning
confidence: 98%
“…Il est permis de penser que le fort intérêt pour les études (86,3 % très élevé ou élevé) porté par nos résultats soit lié à la forte présence des filles (90,2 %). Plusieurs auteurs ont mis en évidence les différences entre les filles et les garçons durant les études (Ducharme, 2012;Royer, 2010;Zhang et Lin, 2020). Roy (2015) rapporte que les filles développent un rapport plus positif envers l'école tout en affichant des taux de réussite supérieurs.…”
Section: Intérêt Au Regard Des éTudesunclassified